1970
DOI: 10.1021/bi00823a003
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic studies of tryptophan synthetase. Interaction of substrates with the B subunit

Abstract: The synthesis of L-tryptophan from indole and L-serine, as catalyzed by the B subunit of Escherichia coli tryptophan synthetase, has been studied with steady-state and rapid-reaction kinetic techniques. Initial velocity measurements of the reaction have been made utilizing the absorption difference between indole and tryptophan at 289 nm. The results were consistent with both a compulsory sequence of substrate addition and with a random, rapid equilibration between enzyme and substrates. Dissociation constants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
69
0

Year Published

1972
1972
2002
2002

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(76 citation statements)
references
References 14 publications
7
69
0
Order By: Relevance
“…The same prediction can now be made for reaction (2) catalyzed by the a-subunit. The analysis of the steady-state kinetics of reaction (3) catalyzed by the B,-subunit favoured an ordered-addition nonequilibrium mechanism, because indole was shown to have only a low affinity for the enzyme [17]. This has been confirmed here.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…The same prediction can now be made for reaction (2) catalyzed by the a-subunit. The analysis of the steady-state kinetics of reaction (3) catalyzed by the B,-subunit favoured an ordered-addition nonequilibrium mechanism, because indole was shown to have only a low affinity for the enzyme [17]. This has been confirmed here.…”
Section: Discussionsupporting
confidence: 72%
“…However, both fluorescence [8] and absorbance [17] measurements have failed to detect indole binding to the enzyme in the absence of L-serine. Equilibrium dialysis studies with ['4C]indole expectedly showed that the affinity of the &subunit for indole is weak (Fig.…”
Section: The Binding Of Indole To the Andsubunit Of Tryptophan Synthasementioning
confidence: 99%
“…The protein concentration was determined spectrophotometrically (e 0.1 %, 1 cm, 280 nm were 2.37 for unfolded lysozyme and 0.58 for β2) The enzymatic activity of β2 was determined according to Faeder and Hammes [17]. Where needed, the inhibitory effect of the residual NDSB present in the assay mixture (determined by measuring the activity of native β2 in the presence of NDSB added at the desired concentration to the assay mixture) was taken into account to determine the renaturation yields.…”
Section: Methodsmentioning
confidence: 99%
“…The conversion of indole and serine to tryptophan (B-reaction; Fig. 1) catalyzed by tmTrpB1 or tmTrpB2 was measured at 80°C by absorption spectroscopy and analyzed using ⌬⑀ 290 (Trp Ϫ indole) ϭ 1.89 mM Ϫ1 cm Ϫ1 (40). Initial velocities were measured as a function of the concentration of either indole or serine, with the other substrate being present at saturating concentrations.…”
Section: Thermotoga Maritima Tryptophan Synthasementioning
confidence: 99%